CONVERSANT WIRELESS LICENSING S.A.R.L. v HUAWEI TECHNOLOGIES CO LTD. Issue 2 (11th September 2019) - ,
Abstract: H1 Patents – European patents – Telecommunications – Standards essential patents – Infringement – Claims for global FRAND licences – Jurisdiction – Justiciability – Whether validity of foreign patents in issue – Stay of proceedings – Forum non conveniens – Whether China the natural and appropriate forum – Service of proceedings – Whether defendants validly served within the jurisdiction – Service out of the jurisdiction – Jurisdictional gateways – Whether good arguable case for a FRAND injunction – Property within the jurisdiction – Serious issue to be tried – Appeal to Court of Appeal